Efficacy of an Aromatic Vinegar in Reducing Psychrotrophic Bacteria and Biogenic Amines in Salmon Fillets (Salmo salar) Stored in Modified Atmosphere Packaging - Jessica Di Toro; Raffaella Branciari; Rossana Roila; Serena Altissimi; Haiyang Jiang; Kang Zhou; Simona Perucci; Michela Codini; David Ranucci (Polish Journal of Food and Nutrition Sciences)
Salmon flesh spoilage can be greatly reduced through the use of preservation methods, using natural products combined with low temperature and packaging. Microbiological and physicochemical characteristics of fresh salmon fillets ( Salmo salar ), sprayed with an aromatic vinegar and stored in modified atmosphere packaging, were investigated. Fillets were kept at 4°C and sampled after 2 h and 3, 7 and 10 days. An untreated control group was used as well. Fish samples were analysed for microbiological (total viable count, Enterobacteriaceae , psychrotrophic microbial count, Pseudomonas spp.) and physicochemical (pH, colour, total volatile basic nitrogen, and biogenic amines) properties. Aromatic vinegar was found to beneficially contribute to the hygienic quality of the salmon, reducing microbial growth during storage and exerting a positive effect, mainly on psychrotrophic loads and Pseudomonas spp. The treatment had a positive effect on biogenic amine levels, showing lower values for histamine, putrescine, cadaverine, and tyramine.